2018
DOI: 10.1186/s13028-018-0431-3
|View full text |Cite
|
Sign up to set email alerts
|

Cetirizine per os: exposure and antihistamine effect in the dog

Abstract: BackgroundCetirizine is an antihistamine used in dogs, but plasma concentrations in relation to effect after oral administration are not well studied. This study investigated cetirizine exposure and the plasma cetirizine concentration-antihistamine response relation in the dog following oral administration of cetirizine.ResultsEight Beagle dogs were included in a cross-over study consisting of two treatments. In treatment one, cetirizine 2–4 mg/kg was administered per os once daily for 3 days. The other treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Treatment protocols included methylprednisolone used in the dose range of 0.2-0.35 mg/kg every other day, and it is well known that corticosteroids have immunosuppressive properties (Bonagura 1995). Moreover, cetirizine was used in the dose 1 mg/kg BID and antihistamine blocks histamine receptors and stabilizes mast cells (Ekstrand et al 2018). The overall gene expression profiles provided from this study showed that cases had a lower within-group variation compared to controls, which may be explained by the similar disease state in cases (i.e., CAD cases were under similar treatment protocols).…”
Section: Unique Study Designmentioning
confidence: 72%
“…Treatment protocols included methylprednisolone used in the dose range of 0.2-0.35 mg/kg every other day, and it is well known that corticosteroids have immunosuppressive properties (Bonagura 1995). Moreover, cetirizine was used in the dose 1 mg/kg BID and antihistamine blocks histamine receptors and stabilizes mast cells (Ekstrand et al 2018). The overall gene expression profiles provided from this study showed that cases had a lower within-group variation compared to controls, which may be explained by the similar disease state in cases (i.e., CAD cases were under similar treatment protocols).…”
Section: Unique Study Designmentioning
confidence: 72%